Fracture criterion of materials subjected to temperature gradient - Shah, Qasim Hussain; Homma, H. (Elsevier BV, 1995)

(untitled)
Fracture tests on fatigue pre-cracked three-point bend specimens of polymethylmethacrylate (PMMA), polycarbonate (PC), and Acrylonitrile-Butadiene-Styrene (AB:S) were conducted to establish the effects of a temperature gradient on the crack initiation fracture toughness in temperature ranges where the fracture toughness of the above-mentioned materials changes steeply. The tests were made on specimens subjected to various temperature gradients while the crack-tip temperature of the specimen was kept constant. Results obtained from the three materials were compared to establish a fracture criterion of the materials subjected to a temperature gradient. The results showed that the fracture toughness of all three materials is influenced in a similar fashion and is dependent upon the degree of the temperature gradient along the crack line.